2012
DOI: 10.1002/syn.21572
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of binding sites for 9‐fluoropropyl‐(+)‐dihydrotetrabenazine ([18F]AV‐133) in a MPTP‐lesioned PD mouse model

Abstract: [¹⁸F]AV-133 PET SUr displayed a high test-retest stability. The SUr significantly declined in the caudate putamen but not in the hypothalamus and midbrain regions after MPTP treatment in the mouse brain. The results obtained for QARG and IHC were consistent and correlated well with the PET imaging studies. On the basis of these concordant results, we find that [¹⁸F]AV-133 should serve as a useful and reliable PET tracer for evaluating nigrostriatal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…Bohnen and colleagues demonstrated that striatal C11-dihydrotetrabenazine binding correlated reliably to clinically rated (UPDRSIII) motor deficits in PD patients [133]. Another VMAT2 radioligand, F-18-AV-133 (a tetrabenazine derivative), is also now used to study nigrostriatal degeneration [142, 143]. While VMAT2 radioligand binding conveniently correlates to nigrostriatal denervation, it does not provide direct evidence of vesicular function or VMAT2 activity.…”
Section: Vmat2 Imaging In Pdmentioning
confidence: 99%
“…Bohnen and colleagues demonstrated that striatal C11-dihydrotetrabenazine binding correlated reliably to clinically rated (UPDRSIII) motor deficits in PD patients [133]. Another VMAT2 radioligand, F-18-AV-133 (a tetrabenazine derivative), is also now used to study nigrostriatal degeneration [142, 143]. While VMAT2 radioligand binding conveniently correlates to nigrostriatal denervation, it does not provide direct evidence of vesicular function or VMAT2 activity.…”
Section: Vmat2 Imaging In Pdmentioning
confidence: 99%
“…Two irregular regions of interest encompassing the whole right and left striatum were drawn on four consecutive slices through the striatum, and the background was readily identifi ed and delineated on the cerebellum guided by detailed CT images and with reference to a stereotaxic brain atlas [26,27] . The results are expressed as SUr, calculated as: (mean striatal uptake − mean cerebellar uptake)/mean cerebellar uptake [22] , and dopaminergic denervation severity (DS) after MPTP treatment, calculated from SUr: (SUr baseline − SUr lesioned )/ SUr baseline [28,29] .…”
Section: Pet Image Acquisition and Analysismentioning
confidence: 99%
“…The small animal 18 F-FP-(+)-DTBZ PET imaging followed a previously published protocol [38], and all PET images were acquired on a preclinical Inveon PET system (Siemens Medical Solutions, Knoxville, TN, USA). Each mouse was subjected to a 20-min static scan under isoflurane anesthesia (1.5% in oxygen gas) 30 min after receiving a single bolus injection of 18 F-FP-(+)-DTBZ (22.76 ± 0.45 MBq in 0.1 mL saline) through a tail vein.…”
Section: Methodsmentioning
confidence: 99%
“…The built-in volume of interests (VOIs) of the striatum and the cerebellum from the MRI template were applied to normalised PET images for quantification. The striatal specific uptake ratio (SUr) was calculated as [(uptake in striatum − uptake in cerebellum)/ (uptake in cerebellum)], where the cerebellum was used as the reference region [38]. …”
Section: Methodsmentioning
confidence: 99%